Factors Associated with Lumbar Puncture Participation in Alzheimer’s Disease Research - Blazel, Madeleine M. (J Alzheimers Dis, 2020)
BACKGROUND: Cerebrospinal fluid (CSF) provides insight into the spectrum of Alzheimer’s disease (AD) pathology. While lumbar punctures (LPs) for CSF collection are generally considered safe procedures, many participants remain hesitant to participate in research involving LPs. OBJECTIVE: To explore factors associated with participant willingness to undergo a research LP at baseline and follow-up research study visit. METHODS: We analyzed data from 700 participants with varying cognition (unimpaired, mild cognitive impairment, and dementia) in the Wisconsin Alzheimer’s Disease Research Center. We evaluated the relationship of demographic variables (age, sex, race, ethnicity, and years of education) and clinical variables (waist-to-hip ratio, body mass index, AD parental history, cognitive diagnosis) on decision to undergo baseline LP1. We evaluated the relationship of prior LP1 experience (procedure success and adverse events) with the decision to undergo follow-up LP2. The strongest predictors were incorporated into regression models. RESULTS: Over half of eligible participants opted into both baseline and follow-up LP. Participants who underwent LP1 had higher mean education than those who declined (p = 0.020). White participants were more likely to choose to undergo LP1 (p < 0.001); 33% of African American participants opted in compared to 65% of white participants. Controlling for age, education, and AD parental history, race was the only significant predictor for LP1 participation. Controlling for LP1 mild adverse events, successful LP1 predicted LP2 participation. CONCLUSION: Race was the most important predictor of baseline LP participation, and successful prior LP was the most important predictor of follow-up LP participation.